2015
DOI: 10.1007/s10072-015-2141-1
|View full text |Cite
|
Sign up to set email alerts
|

Osmophobia in allodynic migraineurs: cause or consequence of central sensitization?

Abstract: Migraine is a primary headache characterized by recurrent attacks of head pain associated with nausea or vomit, photophobia, phonophobia and osmophobia. The presence of osmophobia during migraine attacks seems to be a very specific complaint. Cutaneous allodynia (CA) is very common in migraineurs, and it is the most evident clinical manifestation of central sensitization, a mechanism involved in migraine chronification. This study was aimed at identifying the possible correlation between osmophobia and CA in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 9 publications
1
24
1
Order By: Relevance
“…Migraine headache attacks are accompanied by characteristic symptoms of sensorial dysfunction. Tactile, visual, auditory and olfactory senses are all altered during the migraine attack and generate cutaneous allodynia, photophobia, phonophobia and osmophobia (4)(5)(6)(7)(8). These symptoms are independent from trigeminal nerve input (8) and reflect an altered cerebral cortical processing of sensorial information.…”
Section: Introductionmentioning
confidence: 99%
“…Migraine headache attacks are accompanied by characteristic symptoms of sensorial dysfunction. Tactile, visual, auditory and olfactory senses are all altered during the migraine attack and generate cutaneous allodynia, photophobia, phonophobia and osmophobia (4)(5)(6)(7)(8). These symptoms are independent from trigeminal nerve input (8) and reflect an altered cerebral cortical processing of sensorial information.…”
Section: Introductionmentioning
confidence: 99%
“…There were 13 comparative studies between migraine and other primary headaches or controls without headache, 2,3,5,8,13,14,[17][18][19][20]22,28,31 and 10 that evaluated only migraine patients. 4,6,7,11,15,16,24,26,29,30 As for odour-triggered headache, there were six studies detected, two comparative studies between migraine and other primary headaches, 1,3 two with migraine patients, 7,24 and two case reports. 9,12 However, there were six other studies where pathophysiological aspects of the association between odours and migraine were studied.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, we observed a severe intolerance to odours, pleasant or unpleasant, during headache attacks. 2,[4][5][6][7][8]10,11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] However, a limited number of studies showed that odours may trigger headache attacks in some patients, particularly in migraineurs 1,3,6,7,9,24 and occasionally in cluster headache patients. 12,18 This intolerance to odours is known as osmophobia, and according to two studies that investigated osmophobia in secondary headaches, it occurred during headache attacks only in the primary headaches.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The exact mechanism for osmophobia is not known. In the attack period of headache in individuals, the sense of smell is different, which is related to the neuronal interaction between the olfactory and trigeminal nociceptive system, and this has been suggested to be caused by central sensitization 27, 28 . In mice it has been noticed that, if constantly given smell stimuli, hyperexcitability and anxiety develop as a result of overstimulation of the olfactory system 29,30 .…”
Section: Discussionmentioning
confidence: 99%